IMPACT OF LEADERSHIP STYLES ON PSYCHOLOGICAL DISTRESS AND JOB SATISFACTION AMONG EMPLOYEES IN SABAH - TAMBY OMAR, AISHAH; UNGKU AHMAD, UNGKU NORULKAMAR (MANU Journal of Humanities, 2018)
This research was aimed at determining the effects of toxic leadership on psychological distress and job satisfaction. Data were collected from among 200 employees who are working in the public sector in Kota Kinabalu, Sabah. The empirical results through Pearson Correlation found employees’ psychological distress indicating a positive relationship with toxic leadership. Meanwhile it was found that there is negative relationship between toxic leadership and job satisfaction. This study provides a strong evidence that could help the top management and individuals in the public sector to find strategies to prevent a growth of toxic leadership. Keywords: Toxic leadership, psychological distress, job satisfaction, public sector, leadership.